Studies on the genus Aporcelaimellus Heyns, 1965 (Dorylaimida: Aporcelaimidae) - Redescription of six species studied by Thorne in 1974 (Journal of Nematode Morphology and Systematics, 2012)
Six species ofAporcelaimellus sensu lato studied by Thorne in 1974 are redescribed based on the study of the material deposited in Thornes collection. Descriptions, measurements and illustrations, including line drawings and/or LM pictures, are provided for all of them. A new diagnosis is presented for A. capitatus, with comments on about its identity, and A. angusticollis is regarded as species inquirendae. Three females labelled as A. amylovorus are identified as A. clamus. Six females certainly belonging to type population of A. conoidus are studied. Type material of A. parmus and A. placus is also examined, concluding that both species are very similar to each other and also to A. capitatus, and the identity of these three species is discussed in detail. Two females and two males originally identified as A. sublabiatus are described as belonging to a new species A. thornei.